Dinamika Konflik Kepentingan antara Legislatif dan Eksekutif dalam Proses Tender Konstruksi: Perspektif Administrasi Publik dan Tata Kelola Pemerintahan - Prayoga, Indra Aditya; Kurnia, Encep (Neolectura, 2025)
Conflicts of interest between legislative and executive bodies in public construction tenders continue to undermine transparency and accountability in government procurement. This study aims to identify the main patterns of such conflicts and formulate appropriate mitigation strategies. Using an integrative literature review of 52 scientific publications, thematic analysis was conducted to synthesize findings across various contexts. The results reveal three key patterns: (1) conflicts of interest most frequently occur during the pre-tender and bid evaluation stages through political interference, business affiliations, and informal pressure; (2) existing internal and external oversight mechanisms are insufficient to detect legislative involvement in tender processes, largely due to weak disclosure of beneficial ownership; and (3) ethical standards in public office are not consistently institutionalized, enabling continued collusion between legislative and executive actors in contractor selection. This study proposes a conceptual mitigation model emphasizing structural transparency, independent oversight, and mandatory disclosure of beneficial ownership. The model offers a practical foundation for developing policies aimed at reducing conflicts of interest and strengthening the integrity of public construction procurem